2H and 139La NMR Spectroscopy in Aqueous Solutions at Geochemical Pressures. (25th September 2015) - Ochoa, Gerardo; Pilgrim, Corey D.; Martin, Michele N.; Colla, Christopher A.; Klavins, Peter; Augustine, Matthew P.; Casey, William H.
Abstract: Nuclear spin relaxation rates of 2 H and 139 La in LaCl3 + 2 H2 O and La(ClO4 )3 + 2 H2 O solutions were determined as a function of pressure in order to demonstrate a new NMR probe designed for solution spectroscopy at geochemical pressures. The 2 H longitudinal relaxation rates ( T 1 ) vary linearly to 1.6 GPa, consistent with previous work at lower pressures. The 139 La T 1 values vary both with solution chemistry and pressure, but converge with pressure, suggesting that the combined effects of increased viscosity and enhanced rates of ligand exchange control relaxation. This simple NMR probe design allows experiments on aqueous solutions to pressures corresponding roughly to those at the base of the Earth's continental crust.